#### Answer

$y' = 12x - 10 + 10x^{-3}$
$y'' = 12 -30x^{-4}$

#### Work Step by Step

$y = 6x^{2} - 10x - 5x^{-2}$
$y' = 12x - 10 + 10x^{-3}$
$y'' = 12 - 0 -30x^{-4}$

Published by
Pearson

ISBN 10:
0321999584

ISBN 13:
978-0-32199-958-0

$y' = 12x - 10 + 10x^{-3}$
$y'' = 12 -30x^{-4}$

$y = 6x^{2} - 10x - 5x^{-2}$
$y' = 12x - 10 + 10x^{-3}$
$y'' = 12 - 0 -30x^{-4}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.